Shareholder value creation from Mergers and Acquisitions and its influent factors: evidence from UK in 2002-2011. - Nguyen, Uyen Thi Thao (2012)
This research studies the stock market valuation of mergers and acquisition in the United Kingdom, based on a sample of 205 deals observed from 2002 to 2011. The wealth creation for acquiring companies is examined using a standard event study methodology. Overall, the acquirers benefit from highly abnormal returns at the announcement time. The general results are mainly driven by significant positive abnormal returns accompanying private target transactions. My sample shows significant positive cumulative abnormal returns for the transactions with private targets and transaction financed by cash only. The cross-border transactions sample also yields highly positive returns. Cross-sectional analysis reveals that the key factors for success of M&A are private, profitable firms while the increase of relative transaction size to acquirer and market value of acquirer can destroy shareholders’ wealth. However, the importance of the success drivers is not consistent through cross-border and domestic samples. In the cross-border sample, only status of target and return on equity influence the cumulative abnormal returns. No influential factors associated with the success of M&A are found in the domestic sample.